Naturalization and Labor Market Performance of Immigrants in Germany - Regina T. Riphahn; Salwan Saif (Center for Economic Studies and ifo Institute (CESifo), 2018)
Naturalization may be a relevant policy instrument affecting immigrant integration in host-country labor markets. We study the effect of naturalization on labor market outcomes of immigrants in Germany. We apply recent survey data and exploit a reform of naturalization rules in an instrumental variable estimation. In our sample of recent immigrants, linear regression yields positive correlations between naturalization and beneficial labor market outcomes. Once we account for the endogeneity of naturalization most coefficients decline in magnitude and lose statistical significance: male immigrants' labor market outcomes do not benefit significantly from naturalization. Naturalization reduces the risks of unemployment and welfare dependence for female immigrants. For males and females, the propensity to hold a permanent contract increase as a consequence of naturalization. The results are robust to modifications of samples and the instrument.
Keywords: J61; J15; C26; 330; citizenship; migration; naturalization; labor market outcomes; instrumental variables